Evaluation of influence of the UPOINT-guided multimodal therapy in men with chronic prostatitis/chronic pelvic pain syndrome on dynamic values NIH-CPSI: a prospective, controlled, comparative study - Denis V. Krakhotkin; Volodymyr A. Chernylovskyi; Evgeny E. Bakurov; Johann Sperl (Therapeutic Advances in Urology, 2019)
Background: The aim of this work was to evaluate the influence of UPOINT-guided (Urinary, Psychosocial, Organ-specific, Infection, Neurologic/systemic, Tenderness of skeletal muscles) multimodal therapy in patients with chronic prostatitis (CP)/chronic pelvic pain syndrome (CPPS) on the dynamic values of the National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI) score. Patients and methods: In our study we investigated 110 patients aged 26–68 years with CP/CPPS. We performed digital rectal examination (DRE), pre- and post-massage test (PPMT) urine culture, urine analysis, transrectal ultrasound investigation of prostate, antibiotic susceptibility testing. We divided the patients into the intervention group and the control group which was followed up without any therapy. For the intervention group we offered multimodal therapy based on each predominated positive phenotype. For the urinary phenotype, patients in intervention group received 10 mg alfuzosin. For organ-specific and tenderness domains, the patients of the intervention group received 63 mg Cernilton and 1 g Quercetin. For infection control, the patients of the intervention group received antimicrobial agents according to the results of the post-massage urine culture, antibiotic susceptibility testing and a high level of contamination >10 5  colony-forming units (CFU)/ml. Microbiological assessment of PPMT urine culture was conducted with aerobic and anaerobic methods of cultivation Results: The 110 patients had an average age of 43.9 ± 11.1 years and a median duration of symptoms of 6.21 ± 1.8 months. Of these, 11 patients did not complete the trial and therefore in quantitative terms, the distribution of patients was as follows: 54 in the intervention group and 45 in the control group. The average total NIH-CPSI score before treatment was 29.8 ± 6.1 in both groups. The mean NIH-CPSI of the pain, urinary, and quality of life (QOL) subscores before treatment was 15.1 ± 3.0, 7.4 ± 1.4 and 8.1 ± 2.1, respectively in both groups. After 6 weeks the PPMT urine culture of patients of the intervention group showed the absence or low-level contamination of microorganisms. After conducting the treatment, the mean total NIH-CPSI score in the intervention and control groups was 13.9 ± 2.8 ( p = 0.025) and 29.8 ± 5.8 ( p = 0.18), respectively. The average NIH-CPSI pain subscore in the intervention and control group after treatment was 6.7 ± 1.4 ( p = 0.018) and 15.1 ± 2.8 ( p = 0.21), respectively. The mean NIH-CPSI urinary subscore after treatment in the intervention and control group was 3.22 ± 1.07 ( p = 0.045) and 7.4 ± 1.2 ( p = 0.15), respectively. The average NIH-CPSI QOL subscore after treatment in the intervention and control group was 3.87 ± 1.28 ( p = 0.015) and 8.1 ± 1.9 ( p = 0.35). After multimodal therapy, the prevalence of different UPOINT-positive domains in the patients of both intervention groups did not exceed 14%. Conclusions: The UPOINT clinical phenotypes significantly changed after multimodal treatment, including antibiotics, phytotherapy and α-blockers in patients with CP/CPPS. This combination of treatment showed a decreasing total NIH-CPSI score and an elevation of QOL in patients.